Investigation of the physical and mechanical properties of conventional concrete with partial replacement of sand by bamboo fibers (Research, Society and Development, 2021)
The natural fibers of bamboo are of great interest as reinforcement of polymeric composites, added in small proportions to the concrete mass, aims to increase the compressive strength and improve its structural performance and the turn factor of great importance in its use is the increase of tensile strength making there a control in the propagation of cracks. The present work aims to evaluate the influence of sand substitution by bamboo fibers on the physical and mechanical properties of conventional concrete. Research shows that there was an increase in interest in using natural composites for the reinforcement of concrete, including bamboo fiber. Bamboo fibers because they have relevant mechanical properties, low density, biodegradable and found in nature in abundance, are satisfactory and a great composite to be added in the manufacture of concrete. The materials used were characterized to elaborate the trace of the reference concrete calculated by the ABCP - ACI    method and made concrete with the addition of 2% and 5% of bamboo fibers in its composition. The concretes were tested for compressive strength, modulus of elasticity and direct tensile strength at the ages of 14 and 28 days. The results show that the axial compressive strength did not obtain a significant change, as the percentages of bamboo fibers were added in its composition, although the composite meets the minimum resistance of 20 MPa established by NBR 6118 (2014), and can be used for structural purposes.